Analisa Yuridis Pengangkatan Seorang Mantan Narapidana Korupsi Menjadi Komisaris Bumn - Ni Kadek Lia Sri Padmiani; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
BUMN is a state-owned enterprise where all or most of the capital owned by the state through direct investment comes from separated wealth. In practice, there are still several cases where there is the appointment of a person who has become a former corruption convict to serve as a commissioner of BUMN. The regulation regarding the appointment of BUMN commissioners has been regulated in the provisions of the Law on BUMN. The purpose of this research is to discuss the regulations and legal consequences in the appointment of former corruption convicts to become BUMN commissioners. The type of research that will be used in this research is normative legal research, using a statutory approach and a conceptual approach. There are two sources of legal materials for this research, namely primary and secondary sources. Data collection techniques using literature research techniques. The results of the research explain that the appointment of former corruption convicts to become commissioners can be carried out if the person is not found guilty within 5 years before the nomination. In the appointment of former corruption convicts to become commissioners of SOEs, three conditions must be met, namely formal, material and other requirements. There are two efforts that can be made to the appointment of former corruption convicts to become commissioners of BUMN, namely ordinary legal remedies and extraordinary legal remedies.